United States : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on United States 2013 Article IV Consultation highlights economic policies and development. The economy grew at an annual rate of 1.8 percent in the first quarter of 2013, held down by sharp cuts in public spending, and economic indicators suggest that growth has remained weak in the second quarter of the year. Employment gains averaged about 200,000 over the first half of 2013, up from 180,000 in the previous six months. The unemployment rate continued to fall from its October 2009 peak of 10 percent to 7.6 percent in June 2013, although much of the improvement reflects lower labor force participation.